Designing improved poly lactic-co-glycolic acid microspheres for a malarial vaccine: incorporation of alginate and polyinosinic–polycytidilic acid. (September 2014) - Salvador, Aiala; Igartua, Manoli; Hernández, Rosa María; Pedraz, José Luis
Abstract Vaccination using proteins and peptides is currently gaining importance. One of the major drawbacks of this approach is the lack of an efficient immune response when the antigens are administered without adjuvants. In this study, we have taken the advantage of a combined adjuvant system in order to improve the immunogenicity of the SPf66 malarial antigen. For that purpose, we have combined poly (lactic-co-glycolic) acid microspheres, alginate, and polyinosinic polycytidilic acid. Our results show that microspheres can enhance the IgG production obtained with Freund's complete adjuvant. We have attributed this improvement to the presence of polyinosinic polycytidilic acid, since formulations comprising this adjuvant overcame the immune response from the others. In addition, our microspheres produced both IgG1 and IgG2a, leading to mixed Th1/Th2 activation, optimal for malaria vaccination. In conclusion, we have designed a preliminary formulation with a high potential for the treatment of malaria.